The prince with related documents - Machiavelli, Niccolò 1469-1527 (Bedford/St. Martin's, 2005)
Widely read for its insights into history and politics, The Prince is one of the most provocative works of the Italian Renaissance. Based on Niccolò Machiavelli's observations of the effectiveness of both ancient and contemporary statesmen, the rules for governing set forth in his manual were considered radical and harsh by his contemporaries and shocking to many since then. This major new edition combines an accurate and accessible new translation with important related documents, many of which appear here in English for the first time. In his lucid introductory essay, William J. Connell offers fresh insights into Machiavelli's life, the meaning of his work, the context in which it was written, and its influence over time. Document headnotes, maps, a chronology of Machiavelli's life, questions for consideration, a selected bibliography, and index provide further pedagogical support.